Proximal gastric vagotomy after five years. - Storey, D W (1981)
A follow-up of 93 patients with chronic duodenal ulceration treated by proximal gastric vagotomy without drainage five to nine years previously shows a high incidence of confirmed recurrent ulceration of 16.1%. In addition, there have been patients with transient recurrent ulceration, and a small group with persistent dyspeptic symptoms but in whom no ulcer has been demonstrated. The operation is commendable for its lack of side-effects, but the high incidence of recurrent or persistent symptoms may lead to some reservations about its general application in the treatment of chronic duodenal ulceration.